2010
DOI: 10.1080/00015458.2010.11680618
|View full text |Cite
|
Sign up to set email alerts
|

Belgian and European Experience with the European Homograft Bank (EHB) Cryopreserved Allograft Valves.-Assessment of a 20 Year Activity

Abstract: European Homograft Bank (EHB) has been selecting, preparing, storing and distributing the cryopreserved allograft valves in Belgium and some other European Countries since 1989. It was established in 1988 by a pathologist and the cardiac and vascular surgeons from Belgian and other European centres as an inter-university, international nonprofit association. Due to its neutral behavior and very high quality criteria, European Homograft Bank became one of the prominent heart valve banks in Europe and wider. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The CH thawing process was done in accordance with instructions from the EHB. 7 All tissues were rinsed using 0.9% NaCl before use. A 10-mm Acu-Punch (Acuderm, Fort Lauderdale, Fla) was used to cut circular tissue pieces, as illustrated in Video 1.…”
Section: Graft Tissues Studiedmentioning
confidence: 99%
See 1 more Smart Citation
“…The CH thawing process was done in accordance with instructions from the EHB. 7 All tissues were rinsed using 0.9% NaCl before use. A 10-mm Acu-Punch (Acuderm, Fort Lauderdale, Fla) was used to cut circular tissue pieces, as illustrated in Video 1.…”
Section: Graft Tissues Studiedmentioning
confidence: 99%
“…[2][3][4] Implantation of a competent pulmonary valve in RVOT reconstruction or Ross procedure can be achieved by surgical or transcatheter implantation of cryopreserved human pulmonary homograft (CH) and bovine jugular vein (BJV) grafts. 2,[5][6][7] Recent observations have increased awareness of the risk for IE after successful transcatheter implantation of a stent-mounted BJV conduit. 2,[8][9][10] Comparative studies have showed a significantly higher incidence of IE in BJV grafts compared with surgically implanted CH grafts.…”
mentioning
confidence: 99%
“…The disease is highly fatal because of the infectious process that can lead to sepsis and the destructive process that can have significant consequences with regard to cardiac function. Recent reports on cryopreserved homografts are promising, [9][10][11][12] but there is no substitute for radical debridement in these cases. [13] The use of biological materials for patients with aortic PVE is recommended due to the low reinfection rates caused by the increased penetration of antibiotics in these tissues and the presence of viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…After isolation, donor tissues are examined to exclude lacerations and/or unsuitability sources and graded following macroscopic qualitative evaluation. Antimicrobial procedures are then performed to eliminate bacterial and fungal infective risks with constant control for effective microbe removal [243,244]. Decontaminated tissues are immersed in cryopreserving solutions, usually based on cell culture medium added with a low percentage of the cryoprotectant dimethyl sulfoxide (DMSO).…”
Section: Heart Valve Tissue Banksmentioning
confidence: 99%